Business Growth and Internal Auditing - OWOLABI TITILAYO; OGAN TAMUNOKONBIA PROMISE (CV ODIS, 2022)
Small and Medium Scale Enterprises are generally recognized as the engine of economic growth and development in both developed and developing nations. Despite the theoretical importance of the SME sector, business growth of SMEs has been sluggish in Nigeria. The study employed the survey research design to conduct the research work. The population of the study consists of managers, supervisors, accountants/accounts officer, internal auditors, owner managers and other responsible employees of organized SME retailed shops in Oshodi/Isolo Local Government Area of Lagos State, which was estimated at 150 and a sample size of 109. Data was collected using a structured questionnaire constructed by the researchers. The regression analysis with the aid of SPSS (version 25) was adopted to analyze the data. The regression model indicates that internal auditing function a statistically significantly predict business growth of SMEs in Nigeria F(3,98) = 3.716; P = 0.14. Thus, the study concludes that the internal auditing function has positive and significant impact on business growth of SMEs. The study recommends that SMEs should establish an independent audit function that would lead to value creation and ensuring business growth through efficient risk management and sound internal control system.